Anti-Tumor Activity of Cembranoid-Type Diterpenes Isolated from Nicotiana tabacum L. - Xiao-Long Yuan (Biomolecules, 2019)
Recently, the incidence of hepatocellular carcinoma has increased worldwide. Cembranoid-type diterpenes (CBDs) from tobacco exhibit good antimicrobial, antitumor, and neuroprotective activities. Therefore, in this study, we isolated CBDs from Nicotiana tabacum L. and evaluated their antitumor activity against hepatoma cell lines. Particularly, the anti-tumor activity of α-2,7,11-cyprotermine-4,6-diol (α-CBD) was investigated against HepG2, SMMC-7721, and HL-7702 cells. The MTT assay revealed that α-CBD reduced the formation of cell clones and inhibited the proliferation of hepatocellular carcinoma cells. Morphological observations showed that α-CBD altered cell morphology and membrane permeability before inducing apoptosis. To further explore the antitumor mechanism of α-CBD, flow cytometry and transcriptome analysis were performed using HepG2 cells. The results showed that the number of HepG2 cells increased from 10.4% to 29.8%, indicating that α-CBD inhibits the proliferation of hepatocellular carcinoma cells in the S phase. The gene expression analysis of HepG2 cells treated with α-CBD showed 3068 genes with altered expression, among which 1289 were upregulated and 1779 were downregulated. Apoptosis induced by these differentially expressed genes might be mediated by the p53-PUMA, PI3K-Akt, and IL-1-NF-κB-IAP pathways. Comprehensively, our study shows that α-CBD isolated from N. tabacum L. can be potentially used as a natural antitumor agent.